George Bremner, Graaff-Reinet and “A State of Feeling”, 1848-1859 - Helen Ludlow (Contree, 2012)
This article explores a young Scottish teacher’s attempt to implement the ambitious plans for government education in Graaff-Reinet in the mid 19th century. Designed for the whole population, the New System (or Established System) represents a moment in the racialised history of South Africa when there was an imagination of an inclusive, though very British, education system. The focus of the article is on the identity of an able, well-qualified teacher attempting to fulfil his charge in GraaffReinet, a town of growing affluence and regional importance. While Bremner, as government teacher, proves to be a catalyst for local efforts to improve the quality of education, this is largely a sad story of frustration and failure. Entrenched racial attitudes, class aspirations, and the failure of the state adequately to resource the New System combine to undermine his ambitious efforts and challenge his personal worldview. So too does the teacher’s fiery defence, particularly in his public writing, both of his project and the status and reputation which he believed to be his due.